2017
DOI: 10.3390/app7101091
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Prediction Model of the Temperature Field of a Motorized Spindle

Abstract: Abstract:The thermal characteristics of a motorized spindle are the main determinants of its performance, and influence the machining accuracy of computer numerical control machine tools. It is important to accurately predict the thermal field of a motorized spindle during its operation to improve its thermal characteristics. This paper proposes a model to predict the temperature field of a high-speed and high-precision motorized spindle under different working conditions using a finite element model and test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Shi et al [ 10 ] investigated the effect of thermal expansion on the ball screw feed drive system of a precision boring machine tool, and the theoretical model for thermally induced error along with heat generation characteristics was established. Zhang et al [ 11 ] used the finite element method to predict the temperature field of a high-speed and high-precision motorized spindle under different working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [ 10 ] investigated the effect of thermal expansion on the ball screw feed drive system of a precision boring machine tool, and the theoretical model for thermally induced error along with heat generation characteristics was established. Zhang et al [ 11 ] used the finite element method to predict the temperature field of a high-speed and high-precision motorized spindle under different working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing the temperature field distribution and thermal deformation of motorized spindle, it is found that this method can improve the prediction accuracy. Zhang et al 19 established a temperature field prediction model based on the measured data of the outer surface temperature of motorized spindle, and optimized the heat transfer coefficient by genetic algorithm, which improved the prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature distribution of the motor was calculated, but this coupling was simply unidirectional coupling, and there was a certain difference between the simulation value and the experimental value; the simulation results were inaccurate [11]. Lixiu Zhang et al took the machine motor spindle as the research object, and the prediction model of spindle temperature field for high speed motor under different working conditions was established, and the influence of the cooling system on the heat transfer coefficient of the motor spindle was considered [12].…”
Section: Introductionmentioning
confidence: 99%